Comparison of Compudose®, Ralgro® and Synovex-C® for suckling steer calves - Simms, D.D.; Schalles, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The comparative growth-promoting value of Compudose, Ralgro, Ralgro + Ralgro reimplant, and Synovex-C + Synovex-C reimplant was evaluated on five Kansas ranches with 674 suckling steer calves in seven trials conducted during 1982 and 1983. The Ralgro + Ralgro reimplant program increased gain significantly (P<.05) over controls, with an average improvement of 3.9%. Either a single Ralgro or Compudose implant at branding increased gain about 2.6%. Implanting with Synovex-C produced 1% improvement in gain.
Keywords: Beef; Implants; Gain; Growth